Linking Entrepreneurial Traits and Family Support to Business Autonomy: The Role of Entrepreneurial Behavior in Higher Education Contexts - Intan Aulia; Khusnul Khatimah; Andika Isma; Hajar Dewantara; Salim Diarra (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2025)
This study aims to analyze the influence of entrepreneurial traits and family support on business autonomy through entrepreneurial behavior among students of the Faculty of Economics at Universitas Negeri Makassar. Strong entrepreneurial traits combined with consistent family support are expected to foster higher levels of entrepreneurial behavior, which in turn contributes to the development of business autonomy among students. A quantitative approach was employed, involving 101 respondents selected through proportional random sampling across various study programs within the Faculty of Economics and Business. Data were collected via online questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS), including descriptive analysis, validity and reliability testing, and path analysis. The findings are expected to provide scientific contributions to the field of entrepreneurship, particularly in understanding how individual and environmental factors influence student business independence. Furthermore, the study aims to offer practical recommendations for universities, policymakers, and stakeholders in designing programs that enhance students’ interest and capacity for entrepreneurship.